2011
DOI: 10.1149/1.3505295
|View full text |Cite
|
Sign up to set email alerts
|

Etching of CoFeB Using CO∕NH[sub 3] in an Inductively Coupled Plasma Etching System

Abstract: A CoFeB thin film composing a magnetic tunneling junction of CoFeB/MgO/CoFeB was etched in an inductively coupled plasma ͑ICP͒ etching system using CO/NH 3 gas mixtures, and its etch characteristics were compared with those of the CoFeB thin film etched using Cl 2 /Ar. When Cl 2 /Ar was used to etch the CoFeB thin film, even though its etch rate was faster than that of the CoFeB thin film etched using CO/NH 3 , a rough CoFeB surface could be observed due to the corrosion of the CoFeB surface during exposure to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…Min et al using Cl 2 /Ar plasma reported etched MTJ stacks with clean side-walls 4 . However, the key problem encountered is the material degradation, Cl x species absorbed on the side-walls inducing corrosion of the CoFeB layer 5 . E.H. Kim et al 9 studied the etching of MTJ stacks in HBr/Ar plasma's.…”
Section: And Br Based Plasma Etch Chemistriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Min et al using Cl 2 /Ar plasma reported etched MTJ stacks with clean side-walls 4 . However, the key problem encountered is the material degradation, Cl x species absorbed on the side-walls inducing corrosion of the CoFeB layer 5 . E.H. Kim et al 9 studied the etching of MTJ stacks in HBr/Ar plasma's.…”
Section: And Br Based Plasma Etch Chemistriesmentioning
confidence: 99%
“…Regarding chemical induced damage, Cl radicals from Ar/Cl 2 plasma's have been reported to induce corrosion 5 . The latter triggered the exploration of alternative plasma chemistries.…”
Section: Wet Etch Solutionsmentioning
confidence: 99%
“…In this study, an RF pulse-biasing technique has been applied in the etching of MTJ materials, such as CoFeB and MgO, and W has been used as one of the hard mask materials and its effect on the etch characteristics was investigated in an ICP system using a CO/NH 3 gas mixture, which has been investigated to show high etch rates in previous studies. 30)…”
Section: Introductionmentioning
confidence: 99%
“…8,9 For such device applications, pattering, and therefore etching, the component magnetic materials becomes a critical process for fabricating stable devices. Reactive ion etching (RIE) [10][11][12][13]15 based on chlorine and methanol gases has been used for nanoscale magnetic materials etching. But it shows after-corrosion and oxidation problems.…”
Section: Introductionmentioning
confidence: 99%